2007
DOI: 10.1177/1934578x0700201004
|View full text |Cite
|
Sign up to set email alerts
|

Structure Elucidation of a New Rearranged Abietane Diterpene from a Biologically Active Plant, Salvia eriophora

Abstract: A new rearranged abietane diterpenoid, eriophoroxide (1), was obtained from the root extract of Salvia eriophora Boiss. and Kotschy ex Boiss. Its structure was elucidated by spectroscopic methods and semi-empirical/ab-initio calculations. DNA damaging, cytotoxic and antioxidant activities of the plant extract were tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In addition, teuvincenon B, in addition to having double binding than the compound vilosin A, has an additional hydroxyl group at the carbon 6 position. Numerous studies on the antioxidant activity of rearranged abietane diterpenes and rearranged abietane-like diterpenoids have shown that this class of compounds has significant free radical scanning activity [29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, teuvincenon B, in addition to having double binding than the compound vilosin A, has an additional hydroxyl group at the carbon 6 position. Numerous studies on the antioxidant activity of rearranged abietane diterpenes and rearranged abietane-like diterpenoids have shown that this class of compounds has significant free radical scanning activity [29][30][31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…20, No. 79: [24][25][26][27][28][29][30][31][32][33][34][35][36] various metabolites such as rearranged neoclerodane or abietane diterpenes, sesquiterpenes, triterpenes, steroids, flavonoids and aromatic compounds. These metabolites are responsible for different pharmacological effects.…”
Section: Discussionmentioning
confidence: 99%
“…Ursolic acid (15) and oleanolic acid (16) were isolated from several aerial and root parts fractions (preparative TLC, dichloromethane/acetone: 9/1 solvent system) [24], taraxasterol (17), and lupenone (18) from the aerial part fractions (SCCAPE 41-47-( 12)-3 and SCCAPE 41-47-( 12)-1, respectively, preparative TLC, petroleum ether/dichloromethane: 1/3 solvent system), β-sitosterol (19) and stigmasterol (20) from several aerial part and root fractions (preparative TLC, petroleum ether/dichloromethane: 1/9 and dichloromethane/acetone: 9.8/0.2 solvent systems). As indicated in the literature, diterpenes (10)(11)(12)(13)(14) were isolated from the roots of S. cerino-pruinosa var. cerino-pruinosa and other compounds from its aerial parts (Table S2).…”
Section: Isolation Of the Secondary Metabolitesmentioning
confidence: 99%
“…Turkish Salvia species have been investigated phytochemically and biologically since 1968; many new and known secondary metabolites were isolated from their roots and aerial parts [6,[10][11][12][13][14][15]. Phytochemical studies on Salvia species indicated the presence of various secondary metabolites belonging mainly to terpenoids, flavonoids, phenolic acids, phenolic glycosides, and other groups [6,[10][11][12][13][14][15][16][17][18][19][20]. While the aerial parts of Salvia species contain especially flavonoid-, terpenoid-and steroid-type secondary metabolites, their roots are rich in diterpenoids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation